Students’ Perception on AI Technology : Gemini as a Writing Assistant Tool - Ananda, Dhio Rizky; Salmiah, Maryati (Universitas Muhammadiyah Mataram, 2024)
Student perceptions are very important to educators. Student perceptions lie in how students interpret their educational experiences. Perceptions are shaped by individual experiences, backgrounds and learning styles. AI is becoming increasingly common in many industries, including education, as technology advances. AI is used in education to provide learning content that suits the needs of students. One of them is Gemini. Gemini is a large language model created by Google AI. Gemini is an AI tool that can answer questions in an informative way, even when the questions are open-ended, challenging, or strange. The purpose of this research is to see students' perceptions of the use of AI technology, namely Gemini, as an auxiliary tool in the English Writing process. This research is a qualitative research. This study used the semi-structured interview method, where there are main questions and follow-up questions, where the follow-up questions will be based on the answers to the main questions given at the beginning. This study involved 9 EFL students out of 30 students who had been selected. Most students already have their own AI technology applications, so they think they are reluctant to adapt to AI technology applications like Gemini. But on the other hand, Gemini has many features that are very helpful in the writing process. Although for now students prefer AI technology applications that they have used before compared to Gemini, but when viewed from the perceptions given by students, researchers believe Gemini will be used as a writing tool in the future. This research can provide another option for students to facilitate the writing process so that they do not depend on the AI technology applications they have used before.